PENINGKATAN PENGERAHUAN KADER KESEHATAN MELALUI MEDIA VIDEO DALAM DETEKSI FAKTOR RESIKO TINGGI IBU HAMIL DI PUSKESMAS RIAM - Fajrin, Dessy Hidayati Fajrin; Zakiyya, Affi; Oktafiani , Ellyana (Jurnal Medicare, 2025)
Community health volunteers, especially those involved in Posyandu (Integrated Health Posts), are key agents in promoting public health. One of their important roles is participating in the early detection of pregnancy risk factors. With appropriate training, these volunteers can assist and educate pregnant women, leading to improved awareness and consistent antenatal care. Education through Video media is one of the strategies detecting high-risk factors in pregnant women. This study used a pre-experimental design with a one-group pre-test and post-test approach. The population consisted of 141 community health volunteers in the Jelai Hulu sub-district. A total of 65 respondents were selected as the sample. Bivariate analysis was conducted using the Wilcoxon signed-rank test. The median score of cadre knowledge before being given video media was 45. The median score of cadre knowledge after being given video media was 100. The median increase was 55. Based on the statistical test output, the asymph sig value (2-tailed) was 0.000 smaller <0.05. It can be concluded that there is an increase in health cadre knowledge through video media in detecting high-risk factors for pregnant women.